The COVID-19 Pandemic and the 2020 U.S. Presidential Election - Leonardo Baccini; Abel Brodeur; Stephen Weymouth (Global Labor Organization (GLO), 2021)
What is the effect of the COVID-19 pandemic on the 2020 U.S. presidential election? Guided by a pre-analysis plan, we estimate the effect of COVID- 19 cases and deaths on the change in county-level voting for Donald Trump between 2016 and 2020. To account for potential confounders, we include a large number of COVID-19-related controls as well as demographic and so- cioeconomic variables. Moreover, we instrument the numbers of cases and deaths with the share of workers employed in meat-processing factories to sharpen our identification strategy. We find that COVID-19 cases negatively affected Trump's vote share. The estimated effect appears strongest in ur- ban counties, in states without stay-at-home orders, in swing states, and in states that Trump won in 2016. A simple counterfactual analysis suggests that Trump would likely have won re-election if COVID-19 cases had been 5 percent lower. We also find some evidence that the COVID-19 incidence had a positive effect on voters' mobilization, helping Biden win the presidency.
Keywords: D72; I18; 330; COVID-19; pandemic; elections; political behavior; pre-analysis plan